Mandibular Third Molars in Southern Bulgaria - A Clinical and Radiological Study of 1518 Patients - Petia F Pechalova; Nikolai V Pavlov; Desislava A Konstantinova (Journal of Dental Problems and Solutions - Peertechz Publications, 2017)
The normal eruption time of third molar is after 16 years of age. The impaction rate is higher for third molars when compared with other teeth. The aim: of this study was to evaluate mandibular third molars among southern bulgarians. The objects: of evaluation were 1518 dental patients visited four dental practices in Plovdiv, Bulgaria in the period between May 2013 and May 2016. The presence and position of the left and right mandibular third molar, and the type of performed extraction was investigated (3036 records). Results: From 1518 patients, 851 were females, 667 were males. The mean age of patients was 45.31 years with a standard deviation of 15.64 years. The largest part of the third mandibular molars were properly erupted - 28.43% /863 teeth/ from all studied teeth. The incidence of impaction of mandibular third molars was 18.74% /569 teeth/. The frequency of semiimpacted mandibular third molars was 7.48% /227 teeth/. From both - impacted and semiimpacted teeth, 46.86% /373 teeth - 245 impacted and 128 semiimpacted/ show mesioangular impaction. The next most frequent position was vertical - 29.4% /234 teeth, from which 178 were impacted, and 56 were semiimpacted/. Horizontal was position of 92 impacted and semiimpacted mandibular third molars /11.56%/, 76 teeth /9.56%/ show distoangular impaction, 15 teeth /1.88%/ were positioned buccolingually, 6 teeth /0.75%/ were classifi ed as other than mentioned position. The frequency of agenesis of the mandibular third molars was 6.69% /203 missing buds/. The cases of standard extraction of mandibular third molars, representing 25.69% /780 teeth/. Surgical removal of mandibular third molars was observed in 12.65% /384 teeth/.